Regulating Water Reduction Kinetics on MoP Electrocatalysts Through Se Doping for Accelerated Alkaline Hydrogen Production - Liu, Zhenpeng; Bu, Jun; Ma, Wenxiu; Yang, Bin; Zhang, Lei; Zhong, Hong; Li, Shuangming; Zhang, Jian (Frontiers in Chemistry, 2021)
Owing to its low cost, high conductivity, and chemical stability, Molybdenum phosphide (MoP) has great potential for electrochemically catalyzing the hydrogen evolution reaction (HER). Unfortunately, the development of high-activity MoP still remains a grand challenge in alkali-electrolyzers due to its sluggish water reduction kinetics. Here, we demonstrate a novel strategy for regulating the HER kinetics of the MoP nanowire cathode through partially substituting P atoms with Se dopants. In alkaline solutions, the Se-doped MoP (Se-MoP) nanowire cathode exhibits excellent HER performance with a greatly-decreased overpotential of ∼61 mV at 10 mA cm−2 and a Tafel slope of ∼63 mV dec−1, outperforming currently reported MoP-based electrocatalysts. Experimental and theoretical investigations reveal that Se doping not only facilitates the water dissociation on MoP, but also optimize the hydrogen adsorption free energy, eventually speeding up the sluggish alkaline HER kinetics. Therefore, this work paves a new path for designing MoP-based electrocatalyst with high HER performance in alkaline electrolyzers.